SiO2 substrate and Mo, In codoping effect on crystalline and vibrational characteristics of ZnO sprayed thin films. (September 2015) - Souissi, A.; Mimouni, R.; Amlouk, M.; Guermazi, S.
Highlights: Undoped ZnO and codoped ZnO:Mo:In sprayed thin films on SiO2 at 460 °C. XRD, SEM, EDS, and Raman spectroscopy characterizations. Variable effect of the SiO2 substrate and dopants on the formation of ZnO:Mo:In thin films. Two strong bands, 1LO and 2LO, of high spectral density and of ∼71 and 137 meV energies. Dependence of 2LO phonon mode with average grain sizes, stresses and crystallite sizes. Abstract: Undoped ZnO and codoped ZnO:Mo:In thin films were deposited on an amorphous SiO2 substrate at 460 °C using a (Mo/Zn) molar ratio of 1% and (In/Zn) ratios of 1%, 2%, 3% and 10%. The thin films were characterized by X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), and Raman spectroscopy (RS). The results revealed that the average crystallite sizes ranged from 36.2 to 18.97 nm, decreasing uniformly with the increase of co-doping. They were also lower than the grain size values of 48.29, 51.38, 60.59, 36.76, and 54.52 nm and dependent on the evolution of the residual compressive stress values, namely 0.358, 0.314, 0.569, 0.278 and 0.108 GPa, without and with the co-doping, respectively. The non-uniformities recorded at In 2% could presumably be attributed to the variable effect of the SiO2 substrate and dopants on the formation of ZnO:Mo:In thin films. Raman spectroscopy confirmed the findings from structural analysis, showing that all samples crystallized following the hexagonal Wurtzite single phase. It highlighted the presence of two dominant bands, 1LO and 2LO, whose ∼71 and 137 meV energies were comparable and above the ZnO exciton binding energy of 60 meV. The 2LO band showed marked dependencies on the physicochemical parameters mentioned above. The strong bands noted for optimal co-doping at Mo 1% and In 3% can be used (tested) in various electrical and optoelectronic applications.